(untitled) (Baghdad Science Journal, 2018)
SiO2 nanostructure is synthesized by the Sol-Gel method and thin films are prepared using dip coating technique. The effect of laser densification is studied. X-ray Diffraction (XRD), Fourier Transformation Infrared Spectrometer (FTIR), and Field Emission Scanning Electron Microscopy (FESEM) are used to analyze the samples. The results show that the silica nanoparticles are successfully synthesized by the sol-gel method after laser densification. XRD patterns show that cristobalite structure is observed from diode laser (410 nm) rather than diode laser (532 nm). FESEM images showed that the shape of nano silica is spherical and the particles size is in nano range (? 100 nm). It is concluded that the spherical nanocrystal structure of silica thin films is successfully densified by Doide laser (410 nm).